Technological development and its impact on student reception of a campus radio - Mohamed, Shafizan; Wok, Saodah; Lahabou, Mahaman (Canadian Center of Science and Education, 2017)
In 2011, a study was conducted to look at students’ reception of IIUM.FM, a newly launched online campus radio. Using the Technological Acceptance Model (TAM), the study found that factors such as perceived ease of use, perceived usefulness, and attitude highly influenced audience reception of the online radio. In 2016, a corresponding study, closely based on the original 2011 study was conducted to chart and identify how technological changes and developments have further affected the radio listeners today and whether the factors that determined listenership in 2011 still apply in 2016. The study employed a quantitative research design using the survey method and the questionnaire as the research instrument. A total of 238 respondents were sampled for 2011 and 271 respondents for 2016. Results from the comparisons done between the two studies identified the impact of technological change on the campus radio and offered recommendations and suggestions to the University’s relevant authorities for further improvement.